(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
Menstruation is a normal physiological phenomenon for women which shows their ability to reproduce. Menstrual disorders are common among adolescent girls because they are closely related to the processes involved in the development of female puberty. Therefore, this study aims to determine the relationship between nutritional status, hemoglobin levels, and sleep quality of adolescent girls with irregular menstrual cycles at SMAN 8 Tangerang. The study used a cross-sectional design, the population was all female adolescents who met the inclusion criteria. The subject of this study was 77 respondents who were obtained by using a purposive sampling technique. The instruments used were menstrual cycle questionnaires, sleep quality, and observation sheets for measuring weight, height, and hemoglobin levels. The results of statistical tests using the Chi-Square test at a significance level of 95% (p<0.05). The p-value of the relationship between hemoglobin levels and menstrual cycle is p=0.633, between nutritional status and menstrual cycle p=0.240, and between sleep quality and menstrual cycle p=0.297. Thus, there is no relationship between hemoglobin levels, nutritional status, and sleep quality with the menstrual cycle in adolescent girls at SMAN 8 Tangerang.